SOSIALISASI CALON RELAWAN PRODUK HALAL BAGI MAHASISWA UNIVERSITAS SULTAN AGENG TIRTAYASA - Rochmat, Agus; Yayan Maryani; Ika Rifqiawati; Herayati; Ahmad Bukhari; Ina Indriana; M. Ganiadi (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Students as agents of change in society are required to take part in the halal certification program. The Socialization of Halal Product Process Assistance (PPH) for students is aimed at preparing halal volunteers and halal supervisors who help small and medium-sized businesses to obtain halal certification. The socialization activity was designed in three stages: introduction of halal certification, the flow of registration for filing halal certification, and simulation of preparing administration for filling halal certificates. All of instructors described clearly and providing problems that should be solved. The aim of this activity is to create halal volunteers or supervisors who can assist UMKM in applying for halal certificates.